Cry havoc : [large type] a thriller - Carr, Jack (Carr, Jack (Joint pseudonym). Terminal list (Series), 2025)
"... New thriller introducing young Navy SEAL Tom Reece, a man torn between the blurred lines and allegiances of the military and the increasingly murky world of intelligence. This is how it all began ... 1968. A time of division. A time of civil unrest. A time of war. Just before the Tet Offensive, before President Johnson announces he will not run for reelection, before the assassinations of Martin Luther King Jr. and Bobby Kennedy, as riots and protests rage across the nation, a spy ship is captured by communist forces off the coast of North Korea. As a KGB "illegal" elicits information from a high-ranking NSA official, and teams of special operators infiltrating into Laos, Cambodia, and North Vietnam disappear without a trace, an ambitious Soviet advisor launches an ingenious plan that could forever alter the world balance of power. Tom Reece, a SEAL operator attached to the highly classified and shadowy MACV-SOG is about to be thrust into a bloody battle to discover the truth."--